Influence of varying seed rate and fertilizer levels on yield and quality of linseed (Linum usitassimum L.): INFLUENCE OF VARYING SEED RATE AND FERTILIZER LEVELS ON YIELD AND QUALITY OF LINSEED - S CHANNABASAVANAGOUDA; S A BIRADAR; B M CHITTAPUR; SHAMRAO KULKARNI; S R BALANGOUDAR (Journal of Oilseeds Research, 2018)
A field experiment was conducted during rabi 2016-17 to study the influence of varying seed rate and fertilizer levels on yield and quality of linseed. The result of this experiment revealed that crop sown with seed rate @ 30 kg/ha recorded significantly higher seed yield (909 kg/ha), straw yield (1699 kg/ha), harvest index (0.35), fibre yield (1247 kg/ha), fibre percentage (74 %) and oil yield (331 kg/ha) as compared to seed rate @ 20 kg/ha. While application of 150 per cent recommended dose of fertilizer (RDF) recorded significantly higher seed yield (861 kg/ha), straw yield (1624 kg/ha), harvest index (0.35), fibre yield (1111 kg/ha), fibre percentage (68 %) and oil yield (313.5 kg/ha). Combination of seed rate @ 30 kg/ha with 150 per cent RDF was recorded significantly higher seed yield (923 kg/ha), straw yield (1727 kg/ha), harvest index (0.35), fibre yield (1273 kg/ha), fibre percentage (74 %) and oil yield (335 kg/ha).